5 different meats
3 different cheeses
3 different breads
5x3x3 = 15*3 = 45
there are 45 choices
The sandwich shop offers a total of 45 different sandwich combinations based on the given options of meats, cheeses, and breads. Each sandwich consists of one type of each category.
The question asked is related to the concept of combinations in mathematics. It gives a variety of choices for making a sandwich - 5 types of meats, 3 types of cheeses, and 3 types of breads. Assuming that each sandwich will have one meat, one cheese, and one type of bread, we can calculate the total combinations by multiplying the number of options in each category together. Combinations are used when the order of selection does not matter.
So, the total number of sandwich combinations would be 5 (meats) * 3 (cheeses) * 3 (breads) = 45 different sandwich choices.
#SPJ12
O O and N are similar and congruent.
OM and N are similar but not congruent.
OM and O are similar but not congruent.
Answer:
D.
Step-by-step explanation:
The concept of the square is applied that is the multiplication of the term itself two times.
The equivalent function of is .
The equivalent is the functions that are in different forms but are equal to the samevalue.
Given
(-2m + 5n)² is a function.
To find
The equivalent function of (-2m + 5n)².
We know that this can be written as
(-2m + 5n) x (-2m + 5n)
On multiply, we have
Thus, the equivalent function of (-2m + 5n)² is 4m² - 20mn + 25n².
More about the equivalent function link is given below.
150
extra profit per day.
If it had, instead, lost $350 per day, how much money would it have lost for the week?
Answer:
$2450
Step-by-step explanation:
One week = 7 days
$350 = 1 day
$ 2450 = 7 days(1 week)
350 * 7 = 2450
Equation B: 3y = 3 – 4z
Step 1: –3(y) = –3(15 – 2z) [Equation A is multiplied by –3.]
3y = 3 – 4z [Equation B]
Step 2: –3y = 15 – 2z [Equation A in Step 1 is simplified.]
3y = 3 – 4z [Equation B]
Step 3: 0 = 18 – 6z [Equations in Step 2 are added.]
Step 4: 6z = 18
Step 5: z = 3
In which step did the student first make an error
Answer:
Step 2
Step-by-step explanation:
Where did the -3 from the first equation get simplified to?
Step 1: –3(y) = –3(15 – 2z)
Step 2: 3y = 15 – 2z